The differences in shoulder muscle activity between injured and uninjured rugby players during player- and bag-tackling - Stastny, Petr; Bacakova, Radka; Chytilova, Martina; Tufano, James; Golas, Artur; Masczyk, Adam (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Rugby is a physically demanding game involving multiple body contacts and collisions accompanied by a large number of shoulder injuries, 51% of which occur during tackling. Aim of Study. The aim of this cross-sectional study was to compare shoulder girdle muscle activation between injured (IN) and uninjured (UN) rugby players during bag-tackling and player-tackling. Fourteen rugby players were divided into the injured (IN) (n = 8) and uninjured (UN) (n = 6) groups. The players performed five maximal effort tackles against a tackling bag and against a fellow player. Material and Methods. The tackle momentum, time of impact, and peak surface electromyography amplitude expressed as maximum voluntary isometric contraction (MVIC) were measured on eight muscles: the latissimus dorsi, lower trapezius, pectoralis major, anterior deltoid, serratus anterior, posterior deltoid, middle trapezius, and upper trapezius. Results. The ANOVA revealed significant differences between the IN and UN groups in terms of tackling, with the pectoralis major showing a greater peak in IN (181 ±18% MVIC) compared to UN (141 ± 43% MVIC), the lower trapezius showed showing a greater peak in IN (127 ± 46%MVIC) compared to UN (54 ± 25% MVIC), and the serratus anterior – a greater peak in IN (157 ± 35% MVIC) compared to UN (87 ± 55% MVIC). Conclusions. Injured players display higher excitation levels in the serratus anterior, pectoralis major, and lower trapezius, which support the communal function of the muscles surrounding the shoulder joint during tackling. Testing and treatment of these muscles is recommended for injured rugby players
Keywords: serratus anterior; lower trapezius; pectoralis major; impact; fitness